RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS WEB DENGAN PEMANFAATAN SEO PADA UMKM GADGET HOUSE - Wijaya, Wijaya; Amrizal, Amrizal (Computer Science and Industrial Engineering, 2021)
Gadget House is one of the MSMEs engaged in electronics, namely selling used laptops. The MSME founded in 2016 starting from marketing through the marketplace. The problem faced by Gadget House so far is the absence of supporting facilities for increasing sales using technology that is able to encourage branding on Gadget House so that the existence of Gadget House is still not widely known by the public so that the level of sales has no potential to increase and marketing is trapped in a price war because intense competition in the marketplace. Based on the problems faced, a research was carried out that aims to find out how to design and implement a-based sales information system web. The method used is the SDLC model Waterfall which consists of needs analysis, design, programming, testing, implementation and maintenance. The result of this research is that the existence of a-based sales information system, web namely web e-commerce, can make marketing more targeted without having to compete with competitors in one platform and is expected to increase brand awareness with proper SEO utilization.